Antibiotic control in times of COVID-19 - Chiara Chilet, Christian Manuel (2020)
So far since the COVID-19 pandemic, an increase in the use of antibiotics has been observed, probably one of the main reasons being the uncertainty that exists regarding the therapeutic arsenal against SARS-CoV-2 and the discontinuity of the programs of control of antibiotics. According to the World Health Organization (WHO), infections by resistant germs cause at least 700,000 deaths a year worldwide, and if the necessary measures are not taken in the future, deaths could increase to 10 million by the year. 2050.